Writing skills - Eunson, Baden (Milton, Qld : John Wiley and Sons, 1994)
This book is about: Learning how to write better; The eight parts of speech; Verbs; ...
Keywords: English language; Rhetoric; English language -- Grammar; English language -- Rhetoric